2021
DOI: 10.1186/s12889-020-10080-1
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of local pharmacies to assess asthma control: an Italian cross-sectional study

Abstract: Background Asthma control and monitoring still represents a challenge worldwide. Although the international guidelines suggest the interplay between secondary and primary care services as an effective strategy to control the disease, community pharmacies’ are seldom involved in asthma control assessment. The present cross-sectional study aimed at providing a picture of the relationship between asthma severity and control in community pharmacies within the health district of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…Appropriate use of maintenance medication is key in successful asthma management and optimal control reduces the need for reliever medication. In addition, the role of community pharmacies in supporting the asthma management plan was confirmed in a recent study [ 31 ].…”
Section: Discussionmentioning
confidence: 87%
“…Appropriate use of maintenance medication is key in successful asthma management and optimal control reduces the need for reliever medication. In addition, the role of community pharmacies in supporting the asthma management plan was confirmed in a recent study [ 31 ].…”
Section: Discussionmentioning
confidence: 87%
“…[31][32][33][34] Together with ERs, community pharmacies also represent a first-line health care service, which seems to be more easily accessed by asthmatics when compared to respiratory medicine specialists or general practitioners. 1,35,36 Patients easily refer to the pharmacy to get reliever medications or inhaled drugs in general and bypass the medical follow-up visit. However, a recent large study including community pharmacies confirmed that non-optimal asthma control was more frequent among patients with mild-to-moderate asthma and that low treatment adherence was the only determinant of poorly controlled asthma.…”
Section: Mild-to-moderate Asthma -Unmet Needs and Potential Strategiesmentioning
confidence: 99%
“…However, a recent large study including community pharmacies confirmed that non-optimal asthma control was more frequent among patients with mild-to-moderate asthma and that low treatment adherence was the only determinant of poorly controlled asthma. 36 The above-mentioned information suggests that first-line health care services, namely ERs and community pharmacies, in addition to GPs and specialists, should be involved in detecting asthmatic patients at risk of asthma exacerbations due to inadequate adherence to pharmacological treatment and follow-up programmes. In fact, a recent study reported that among patients admitted to the ER for an asthma attack, most were classified with white to yellow codes, according to the triage severity scoring system; 31 this suggests that those admissions were related to poorly controlled and not to truly severe asthma, and were probably preventable by simply optimizing treatment adherence and by providing patients with a personalized asthma action plan.…”
Section: Mild-to-moderate Asthma -Unmet Needs and Potential Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…El ACT presenta una validación más detallada en sus puntos de corte, una puntuación de 20 o superior indica asma controlada, de 16 a 20 parcialmente controlada, e inferior a 15 un asma mal controlada. Se han reportado estudios como el de Carminati et al (17) (2021) que demuestran que el uso del ACT podría ser una herramienta muy útil para evaluar el grado de control del paciente asmático desde la farmacia comunitaria. En este estudio los 57 FC italianos participantes evaluaron el grado de control del asma de 584 pacientes, identificando las puntuaciones por debajo de 16 puntos con pacientes asmáticos que no usaban un tratamiento regular de base.…”
Section: Detección De Situaciones De Riesgo Y De Pacientes Con Asma Poco O Mal Controladaunclassified